Vygotsky, Wittgenstein, and sociocultural theory. (20th June 2018) - Newman, Stephen
Abstract: This paper considers the use made of Vygotsky's work by many who take a sociocultural perspective and, in particular, by those who use his work to advance a particular view of second language acquisition and the 'silent period'. It is argued that Vygotsky's account as represented in Thought and Language (Vygotsky, 1986 ) needs to be thought of as consisting of two distinct aspects: first, the observations he made (or claimed to have made) and, second, the theoretical account he proposed to explain them. It is shown that some of Vygotsky's observations are problematic but that, even if they are accepted, Vygotsky's theoretical account suffers from fundamental difficulties. Thus the support claimed from Vygotsky in accounts of second language acquisition is misplaced, first because of those difficulties and, second, because many who claim support from Vygotsky, do not need or even use his theory but instead focus their attention on his empirical observations and assume incorrectly that if their own empirical observations match Vygotsky's, then Vygotsky's theory can be accepted. Wittgenstein's later philosophy is shown to provide a perspective which dispels confusions about, and gives us a clearer insight into, the issues.